2018
DOI: 10.1021/acs.jpcc.7b12767
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Polymorphism in Aluminum Carbide Cluster Anions AlnC2: Formation of Acetylide-Containing Structures

Abstract: Aluminum carbide cluster anions Al n C 2 − (n = 5−13) were observed as the most dominant products in the gas-phase reactions of laser-ablated Al n − with organic molecules, such as methanol, ethanol, pentane, acetonitrile, or acetone. Density functional theory calculations predicted two possible isomeric structures for Al n C 2 − : isomers in which two carbons are dissociated (type D) as in the case of the bulk aluminum carbide and novel isomers in which two carbons form an acetylide-like C 2 unit. The latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
0
14
1
Order By: Relevance
“…Mass spectrometry and theoretical calculations on neutral aluminum–carbon clusters indicated that the small neutral aluminum–carbon clusters prefer to form structures containing a C 2 unit . Photoelectron spectroscopy and density functional theory studies on dicarbon-doped aluminum cluster anions suggested that those clusters exhibit two structure types in terms of whether two carbon atoms dissociate or not . A series of small aluminum–carbon clusters have been investigated using anion photoelectron spectroscopy and theoretical calculations, and it was found that the Al 4 C – anion has a planar tetracoordinate carbon (ptC) structure with D 4h symmetry .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry and theoretical calculations on neutral aluminum–carbon clusters indicated that the small neutral aluminum–carbon clusters prefer to form structures containing a C 2 unit . Photoelectron spectroscopy and density functional theory studies on dicarbon-doped aluminum cluster anions suggested that those clusters exhibit two structure types in terms of whether two carbon atoms dissociate or not . A series of small aluminum–carbon clusters have been investigated using anion photoelectron spectroscopy and theoretical calculations, and it was found that the Al 4 C – anion has a planar tetracoordinate carbon (ptC) structure with D 4h symmetry .…”
Section: Introductionmentioning
confidence: 99%
“…11 Photoelectron spectroscopy and density functional theory studies on dicarbon-doped aluminum cluster anions suggested that those clusters exhibit two structure types in terms of whether two carbon atoms dissociate or not. 12 A series of small aluminum−carbon clusters 13−18 have been investigated using anion photoelectron spectroscopy and theoretical calculations, and it was found that the Al 4 C − anion has a planar tetracoordinate carbon (ptC) structure with D 4h symmetry. 19 In addition to the ptC structures, 20 aluminum−carbon clusters were predicted to form many interesting structures 21−26 such as planar pentacoordinate carbon structures, 27 starlike structures, 28 or carbon endohedral stable structures.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the calculated level of theory was based competence of the method to predict the structural properties of Al-containing clusters. [4,24,29] We have also compared several experimental observables against the calculated data to validate the above method. [4,29] The optimization of each structure was further confirmed without any imaginary harmonic vibrational frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…[4,24,29] We have also compared several experimental observables against the calculated data to validate the above method. [4,29] The optimization of each structure was further confirmed without any imaginary harmonic vibrational frequencies. All calculations were performed using the TURBOMOLE program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation